Metric and morphological assessment of facial features: A study on three European populations - Ritz-Timme, S.; Gabriel, P.; Tutkuviene, J.; Poppa, P.; Obertová, Z.; Gibelli, D.; De Angelis, D.; Ratnayake, M.; Rizgeliene, R.; Barkus, A.; Cattaneo, C. (Forensic science international, 2011)
Identification from video surveillance systems is becoming more and more frequent in the forensic practice. In this field, different techniques have been improved such as height estimation and gait analysis. However, the most natural approach for identifying a person in everyday life is based on facial characteristics. Scientifically, faces can be described using morphological and metric assessment of facial features. The morphological approach is largely affected by the subjective opinion of the observer, which can be mitigated by the application of descriptive atlases. In addition, this approach requires one to investigate which are the most common and rare facial characteristics in different populations. For the metric approach further studies are necessary in order to point out possible metric differences within and between different populations. The acquisition of statistically adequate population data may provide useful information for the reconstruction of biological profiles of unidentified individuals, particularly concerning ethnic affiliation, and possibly also for personal identification. This study presents the results of the morphological and metric assessment of the head and face of 900 male subjects between 20 and 31 years from Italy, Germany and Lithuania. The evaluation of the morphological traits was performed using the DMV atlas with 43 pre-defined facial characteristics. The frequencies of the types of facial features were calculated for each population in order to establish the rarest characteristics which may be used for the purpose of a biological profile and consequently for personal identification. Metric analysis performed in vivo included 24 absolute measurements and 24 indices of the head and face, including body height and body weight. The comparison of the frequencies of morphological facial features showed many similarities between the samples from Germany, Italy and Lithuania. However, several characteristics were rare or significantly more or less common in one population compared to the other two. On the other hand, all measurements and indices, except for labial width and intercanthal-mouth index showed significant differences between the three populations. As far as comparisons with other samples are concerned, the three European Caucasian samples differed from North American Caucasian, African and Asian groups as concerns the frequency of the morphological traits and the mean values of the metric analysis. The metric and morphological data collected from three European populations may be useful for forensic purposes in the construction of biological profiles and in screening for personal identification.